Justice And Legal Certainty In The Imposition Of Narcotics (Bekasi District Court Decision Study number 217/Pid.Sus / 2025 / PN Bks) - Maswandi, Maswandi (Legalpreneur Journal, 2025)
Law enforcement against narcotics crime requires a balance between legal certainty, justice, and expediency. This study aims to analyze how the principle of justice and legal certainty is applied in the Bekasi District Court decision number 217/Pid.Sus/2025 / PN Bks against two defendants, namely Bayu Setiawan alias Bontot and Ayub Ferdiansyah alias Ayub, who were proven to have committed the crime of conspiracy to sell Class I narcotics. This research uses normative juridical method with case approach. Based on the analysis, the panel of judges sentenced the defendants to imprisonment for eleven years in accordance with Article 114 paragraph (2) in conjunction with Article 132 paragraph (1) of Law No. 35 of 2009 on narcotics. The decision reflects the application of the principle of legal certainty because it is based on valid evidence and the elements of the offense are met. However, from the aspect of substantive justice, the verdict does not fully reflect the rehabilitative approach for users and intermediaries, so the repressive approach is still dominant.